The Delphi Method and Scientific Research - Gaytán Cortés, Juan (Mercados y Negocios, 2024)
Science has evolved to think about space, time and the relations of subject and object, as a highly abstract regulatory idea and not just as a synonym for models and norms to be followed. The paths of science must guarantee all agreements, those based on procedures using philosophy and mathematical concepts for the explanation of reality (positivism) and also those based on principles to understand and interpret social phenomena in their reality, relationships, values, attitudes, beliefs, habits and representations.